1998
DOI: 10.1074/jbc.273.23.14495
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Association of Calcium Channel α1B and β Subunits during Rat Brain Ontogeny

Abstract: Calcium functions as an essential second messenger during neuronal development and synapse acquisition. Voltage-dependent calcium channels (VDCC), which are critical to these processes, are heteromultimeric complexes composed of ␣ 1 , ␣ 2 /␦, and ␤ subunits. ␤ subunits function to direct the VDCC complex to the plasma membrane as well as regulate its channel properties. The importance of ␤ to neuronal functioning was recently underscored by the identification of a truncated ␤4 isoform in the epileptic mouse le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 73 publications
9
72
0
1
Order By: Relevance
“…Indeed, activation of PKA was shown to antagonize ethanol modulation of N-and P/Q-type VGCCs in PC12 cells (Solem et al, 1997). N-type channel subunit composition modifications during development could be an additional explanation for the different sensitivity to ethanol throughout maturation (Jones et al, 1997;Vance et al, 1998;Lin et al, 1999;Pan and Lipscombe, 2000) Our findings are consistent with several reports indicating that these channels are important targets of ethanol. Through their modulation, ethanol inhibits dopamine release from rat striatal synaptosomes (Woodward et al, 1990), vasopressin release from rat neurohypophysial nerve terminals (Wang et al, 1991), and depolarization-induced rises in [Ca 2ϩ ] i in PC12 cells (Solem et al, 1997).…”
Section: Ethanol Affects Glutamatergic Synaptic Currents In Neonatal supporting
confidence: 81%
“…Indeed, activation of PKA was shown to antagonize ethanol modulation of N-and P/Q-type VGCCs in PC12 cells (Solem et al, 1997). N-type channel subunit composition modifications during development could be an additional explanation for the different sensitivity to ethanol throughout maturation (Jones et al, 1997;Vance et al, 1998;Lin et al, 1999;Pan and Lipscombe, 2000) Our findings are consistent with several reports indicating that these channels are important targets of ethanol. Through their modulation, ethanol inhibits dopamine release from rat striatal synaptosomes (Woodward et al, 1990), vasopressin release from rat neurohypophysial nerve terminals (Wang et al, 1991), and depolarization-induced rises in [Ca 2ϩ ] i in PC12 cells (Solem et al, 1997).…”
Section: Ethanol Affects Glutamatergic Synaptic Currents In Neonatal supporting
confidence: 81%
“…Insulin-secreting cell lines express functional N-type Ca 2ϩ channels, which are important for insulin secretion (17,43); however, it has not been clearly established whether primary pancreatic ␤-cells express this type of channel, and their role in the glucose-induced insulin secretion is still under debate (12,22,34,43,45). We observed expression of ␣1B mRNA and their proteins in neonatal and adult ␤-cells.…”
Section: Discussionmentioning
confidence: 63%
“…Neurons and myocytes exhibit a changing pattern of Ca 2ϩ channel expression during development (19,24,31,45). This type of regulation has not been previously reported in pancreatic ␤-cells, and it is interesting because it could be related to the functional maturation of ␤-cells.…”
Section: Discussionmentioning
confidence: 76%
“…Given that the Ca V ␥ 2 /␥ 3 subunits significantly decrease N-type channel activity and expression, they might provide a negative feedback on current amplitude and neurotransmission. In addition, it has been reported that N-type channel expression is an important cue in the genesis of synaptic transmission (Jones et al, 1997;Vance et al, 1998). Therefore, it is also possible that Ca V ␥ 2 /␥ 3 might play a role as a negative regulator for N-type channel expression during brain ontogeny.…”
Section: Inhibition Of Channel Targeting To the Cell Membranementioning
confidence: 99%